PROGNOSTIC VALUE OF WHITE MATTER CHANGES IN PATIENTS WITH TIA OR STROKE: A POPULATION-BASED STUDY. (29th November 2012) - Simoni, M; Li, L; Mehta, Z; Rothwell, PM
Abstract : Background: White matter changes (WMC) on CT or MR brain imaging are common in TIA and stroke patients. Inconsistent associations, never so far researched in stroke and TIA population-based cohorts, have been reported between WMC and severity of stroke, disability, risk of recurrent stroke and death. Methods: In consecutive TIA and stroke patients, semi-quantitatively rated WMC on CT and MRI, were related to premorbid disability (modified Rankin Score—mRS), baseline MMSE, risk of recurrent stroke, disability at 1 year and death during follow-up. Logistic and Cox regression analyses were adjusted for age, sex, and vascular risk factors. Results: 1840 patients had MRI (520) and/or CT (1717). WMC were associated with worse premorbid mRS (OR for mRS>2, given WMC mod/severe on ARWMC scale=1.82, 95% CI 1.35 to 2.45, p=<0.0001) and with risk of worsening mRS at 1 year (OR=1.36, 1.02–1.83, p=0.04). Analyses of Barthel index domains showed associations with reduced pre-morbid mobility and continence. WMC were associated with baseline MMSE <24 (OR=1.71, 1.19–2.47, p=0.004) and with higher risk of death during follow-up, particularly in patients aged <75 years (adjusted HR=1.70, 1.08–2.67, p=0.02). No association emerged with recurrence of ischaemic stroke, although WMC did predict intracerebral haemorrhage (adjusted HR=2.83, 1.17–6.85, p=0.02). Conclusions: In TIA or stroke patients, WMC are associated with pre-morbid disability and baseline cognitive impairment and predict progression of disability and risk of death at follow-up, independent of age, sex and vascular risk factors.